Nucleation and growth of single layer graphene on electrodeposited Cu by cold wall chemical vapor deposition. (1st February 2017) - Das, Shantanu; Drucker, Jeff
Abstract: The nucleation density and average size of graphene crystallites grown using cold wall chemical vapor deposition (CVD) on 4 μ m thick Cu films electrodeposited on W substrates can be tuned by varying growth parameters. Growth at a fixed substrate temperature of 1000 °C and total pressure of 700 Torr using Ar, H2 and CH4 mixtures enabled the contribution of total flow rate, CH4 :H2 ratio and dilution of the CH4 /H2 mixture by Ar to be identified. The largest variation in nucleation density was obtained by varying the CH4 :H2 ratio. The observed morphological changes are analogous to those that would be expected if the deposition rate were varied at fixed substrate temperature for physical deposition using thermal evaporation. The graphene crystallite boundary morphology progresses from irregular/jagged through convex hexagonal to regular hexagonal as the effective C deposition rate decreases. This observation suggests that edge diffusion of C atoms along the crystallite boundaries, in addition to H2 etching, may contribute to shape evolution of the graphene crystallites. These results demonstrate that graphene grown using cold wall CVD follows a nucleation and growth mechanism similar to hot wall CVD. As a consequence, the vast knowledge base relevant to hot wall CVD may be exploited for graphene synthesis by the industrially preferable cold wall method.